Age associated changes in the histochemistry of vas deferens in Gaddi goat (Capra hircus) - ARCHANA, ARCHANA; KATIYAR, R S; SHARMA, D N; FAROOQUI, M M (The Indian Journal of Animal Sciences, 2011)
The study was conducted on 30 male Gaddi goats (one-day old to 73 months old), divided into 3 groups viz.; prepubertal (one-day old to 18 months to 60 months) animals with at least 10 animals in each group. The study revealed mild to moderate PAS and DNA reaction in the prepubertal goats, becomes intense in the pubertal and more preponderant in the post-pubertal animals. Lipid granules were more concentrated in the prepubertal animals than in pubertal and post-pubertal animals. The acid and alkaline phosphatase reactions were moderate in prepubertal animals but strong in the epithelium of vas deferens of pubertal animals. A strong positive bromophenol blue reaction was observed in the glandular epithelium of ampulla in pubertal and postpubertal animals.